Interarticulatory Timing and Celtic Mutations. (1st January 2020) - Eska, Joseph
After providing an analysis of Celtic phonology as per the approach to phonology known as Laryngeal Realism, this paper addresses the differing realizations of the two mutations common to Goidelic and Brittonic, the first lenition and nasalization. It is proposed that differences in interarticulatory timing between consecutive segments led to the attested differing realizations of these mutations. Some attention is also paid to the differing realizations of nasalization between Irish and Scottish Gaelic.